Learning Organization in Education: Τhe Case of the Greek Postgraduate Theses - Οικονόμου, Κωνσταντίνος; Λαζαρίδου, Αγγελική (Education Sciences, 2022)
In this paper we analyze 69 master’s theses written until the end of 2020 on the subject “The learning organization in education”. These theses are an indicator of this kind of research in Greece, in terms of: the evolution of the concept’s approach and of the researched fields; the methodology; as well as the purpose of the research and its results, i.e. the depiction of reality. After some preliminary remarks, we present in detail and comment on the various trends identified in the postgraduate theses (demographic, methodological and thematic). We conclude by a summary our findings and a reference to the perspective of this research.